Tablet or capsule form of generic mycophenolate mofetil (My-Rept®) after liver transplantation: a prospective randomized trial - Kim JM; Oh JW; Kim S; Rhu J; Lee JS; Kim KS; Choi GS; Joh JW (Dove Medical Press, 2019)
Jong Man Kim,* Jong Wook Oh,* Sangjin Kim, Jinsoo Rhu, Ji Soo Lee, Kyeong Sik Kim, Gyu-Seong Choi, Jae-Won JohDepartment of Surgery, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, Republic of Korea*These authors contributed equally to this workBackground: Tablet and capsule forms have advantages and disadvantages in the market. Generally, the tablet form (500 mg) of mycophenolate mofetil (MMF) is more convenient for drug ingestion and more cost-effective than the capsule form (250 mg). We examined the efficacy and safety of MMF in its different forms combined with tacrolimus in liver transplant recipients.Methods: A randomized controlled trial was performed to compare the efficacy and safety between the tablet form of MMF (tablet group) and the capsule form of MMF (capsule group) in liver transplant patients. One hundred sixteen patients were enrolled in the present study from 2014 to 2017. Fifty-six patients in the full-analysis set (FAS) population were in the capsule group and 60 were in the tablet group. The primary endpoint was incidence of biopsy-proven acute rejection (BPAR) by 24 weeks after liver transplantation (LT). Secondary endpoints were patient survival, serum creatinine level, and adverse events (AEs).Results: In the per-protocol population, 45 patients were in the tablet group and 49 were in the capsule group. There were no statistically significant differences in MMF dose, mycophenolic acid trough level, and tacrolimus trough level between the two groups. The incidence of BPAR at 24 weeks after randomization was 6.7% in the tablet group and 6.1% in the capsule group (P=0.627). All patients with BPAR responded well to steroid pulse therapy and increased tacrolimus. Serum creatine level and eGFR were not different between the two groups. The incidence of serious AEs was 7.2% in the tablet group and 7.6% in the capsule group, and none were related to formulation. There was no significant difference in incidence of discontinuations or serious AEs between the two groups.Conclusion: The present study suggests that the new tablet formulation can be a useful treatment option to maintain a consistent systemic exposure level of MMF, which may help reduce graft failure in liver transplant patients.Keywords: tacrolimus, liver transplantation, efficacy, immunosuppression